Revisiting posttraumatic growth theory: A narrative review integrating individual, collective, and cultural dimensions - Siti Hajar Sri Hidayati; Akhsanul Khalis; Shelvya Fauziah Ardi (Empathy : Jurnal Fakultas Psikologi, 2025)
Posttraumatic Growth (PTG) has long been viewed as an individual psychological process shaped by cognitive and emotional struggle after trauma. However, recent scholarship highlights the importance of social, communal, and cultural factors that remain underrepresented in earlier reviews. This study follows a narrative review methodology with purposive sampling that synthesizes peer-reviewed studies published between 2020 and 2025 to examine how PTG theory has expanded beyond individual transformation. A structured search across major databases resulted in 20 studies meeting purposive inclusion criteria. Findings reveal two converging trends: the persistence of individual-centric PTG models and the growing recognition of collective and cultural pathways, such as social support, shared rituals, and culturally grounded meaning-making. Integrating these strands, this review proposes a multilayered ecological model positioning individual, relational, collective, and cultural dimensions of PTG. The review underscores the need for culturally sensitive PTG frameworks and community-based interventions, offering a more inclusive theoretical foundation for understanding trauma recovery.